Analisis kinerja keuangan perusahaan sub sektor hotel dan fasilitas rekreasi yang tercatat di Bursa Efek Indonesia tahun 2018-2022 - Ni’amil Ridha Maula (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The world economy continues to chane rapidly due to various reasons, such as technological development, globalization, climate chane, and major events such as pandemics. In this uncertain business environment, the survival of a company is highly dependent on management’s ability ti maintain the company’s work performance and financial stability. The importance of financial performance is not limited to the internal aspects of management, but is also a major consideration for investors, creditor, government and other stakeholders. This study aims to describe and analyze the financial performance of the hotel and recreational facilities sub-sector listed on the Indonesia Stock Exchange in 2018-2022, with descriptive quantitative research methods. Researchers use four financial ratios to measure financial performance, namely the liquidity ratio, solvency ratio, profitability ratio and activity ratio. The results show that of the 4 ratios used by the hotel and recreational facilities sub-sector companies listed on the IDX for the 2018-2022 period are good, because there are 3 positive ratios and only 1 negative ratio. so that to achieve the positives of the four ratios, it needs to be improved both from internal and external to further improve its financial performance and to be more attractive to potential investors. Keywords: financial performance, financial ratios, company
Reuplod Repository Ratna 17 Juli 2026 Validasi dan Finalisasi Ratna 17 Juli 2026
Keywords: financial performance; financial ratios; company